The Impact of the “Talk for Teens” Education Program on Improving Knowledge of Reproductive Health and Sexually Transmitted Infections Among Adolescents at SMPN Garut - Airin Rizki Mulyani; Adelse Prima Mulya; Mamat Lukman (CV. Utami, 2026)
Adolescents are population group that is highly vulnerable to reproductive health problems and sexually transmitted infections (STIs) due to limited knowledge and inadequate preventive behaviors. A School Health Nursing (SHN) assessment at SMPN 6 Garut revealed several students experiencing reproductive health issues such as vaginal discharge, genital itching, and uneven understanding of STI prevention. This study aimed to determine the effect of reproductive health and STI prevention education on improving adolescents’ knowledge at SMPN 6 Garut, Garut City District. This study employed a pre-experimental one-group pretest–posttest design involving 315 students (150 males and 165 females). The intervention titled “Talk for Teens – Not Just Growing, but Growing Healthily” was delivered through interactive lectures, group discussions, and audiovisual media. Data were analyzed using the Wilcoxon Signed Rank Test. The average knowledge score among girls increased from 5.21 to 6.76 (an increase of 1.55 points; p < 0.01), while the score among boys increased from 8.87 to 8.89 (an increase of 0.02 points; p > 0.05). The results indicate a significant difference among females but not among males. Interactive reproductive health education effectively improved female students’ knowledge regarding hygiene and STI prevention, though it showed no significant impact among male students. It is recommended that schools and community health centers collaborate to conduct ongoing, gender-based educational programs to enhance adolescent health literacy in Garut City.